Impact of Some Pesticides on Total Counts of Soil Non-Symbiotic Nitrogen-Fixing Bacteria, Particularly Azotobacter sp - Khudhur, Nashmeel Saeed; Sarmamy, Abdul-ghany Omer Ismaeel (Sulaimani Journal for Pure and Applied Sciences, 2016)
A pot experiment was conducted to evaluate the effect of glyphosate herbicide (n- phosphonomethyl glycine), mancozeb fungicide ([[1,2-ethanediylbis- [carbamodithioato]] (2-)] manganese mixture with [[1,2-ethanediylbis- [carbamodithioato]]-(2- )] zinc) and diazinon insecticide (O, O-diethyl O-[6- methyl-2- (1-methylethyl)- 4-pyrimidynyl]), three soil orders and two soil moisture contents (50% and 100% of field capacity) and their combinations on soil total non-symbiotic nitrogen-fixing bacteria particularly Azotobacter sp. counts. This experiment last for two months from the 6 th of Jun until the 8 th of August 2011 with five sampling periods at biweekly intervals. Factorial experiment (4×3×2) with Completely Randomized Design (CRD) and three replications was used and the means were compared using Revised Least Significant Differences (R.LSD) at the level of significant of 0.05. Significant results were obtained at the last two scheduled period’s sampling of 4 th and 5 th , and the results showed that: Mancozeb fungicide decreased total Azotobacter sp.; Diazinon insecticide decreased both total non-symbiotic nitrogen-fixing bacteria and total Azotobacter sp.; Agholan soil (order Entisols) showed the greatest increase in soil total non-symbiotic nitrogen-fixing bacteria. 50% soil moisture content revealed the greatest reduction total Azotobacter sp. while, 100% soil moisture content showed the greatest increase in soil total Azotobacter sp. count. The combinations among: glyphosate, Agholan soil and 100% moisture combination showed the greatest reduction in total non-symbiotic nitrogen-fixing bacteria and total Azotobacter sp.
Keywords: Soil pollution; Pesticides; Nonsymbiotic; nitrogenfixing bacteria; Azotobacter sp